ANALYSIS OF TRACHEOBRONCHIAL FOREIGN BODIES WITH RESPECT TO SEX, AGE, TYPE AND PRESENTATION - Asif, Muhammad; Shah, Shahid Ali; Khan, Farida; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2007)
Background: Foreign body inhalation is one of the life threatening emergencies. It may happen at any age, however, most of these accidents occur in children especially below the age of five. Methods : This prospective study was done at Department of Otolaryngology, Head and Neck Surgery, Ayub Teaching Hospital, Abbottabad, from 1 January 2003 to 30 June 2005. A total of Eighty one patients, referred from the casualty and Paediatric unit with suspicion of tracheobronchial foreign body were included in the study. Results: Eighty one were studied. Fifty (61.7%) were male and thirty one (38.3%) were female. Sixty three (77.8%) were below five years, thirteen (16%) were between five and fifteen years and five (6.2% ) were above fifteen years. Sixty seven patients (82.7% ), presented mainly with chocking, while fifty nine patients (72.8%) had stridor and forty five patients (55.6%) had cough at initial presentation. Seventy two (88.9%) patients had decreased air entry and forty two (51.9%) had wheeze on auscultation, whereas cyanosis was noticed in five (6.2%) patients. Peanut was the commonest foreign bdy, retrieved in forty five patients (55.6%). Other foreign bodies were whistle (18.5%), maize seed (13.6%), bean seed (6.2 %), nuts (2.5%), sewing needle with thread, dice and denture (1.2%) each. Conclusions: Foreign body inhalation is more common in male patients, mostly below five years of age. Chocking is the commonest symptom and decreased air entry on auscultation is the typical examination finding. Peanut has been found to be the commonest type of foreign body. Key words: Tracheobronchial, Foreign body, Peanut.